Implementasi Supervisi Akademik di SMP Negeri 1 Bancak Kabupaten Semarang - Setyo Budi Utomo; Yari Dwikurnaningsih; Sophia Tri Satyawati (Universitas Muria Kudus, 2021)
This study aims to determine the implementation of academic supervision in SMP Negeri 1 Bancak, Semarang Regency. This research was conducted through a qualitative descriptive approach, with the research subject being purposive sampling. Data collection was carried out using interview techniques and documentation studies at SMP Negeri 1 Bancak, Semarang Regency. The results of the study stated that the implementation of academic supervision was carried out with the stages of planning, implementing, evaluating and following up. The emphasis of the implementation of supervision at SMP Negeri 1 Bancak is the implementation of device supervision by the principal and academic supervision in the form of classroom observation activities. There are several supporting factors and obstacles in the implementation of academic supervision which are then explained by the researchers as an effort to solve the problems found